A cross-national analysis of parental involvement and student literacy. (June 2013) - Hampden-Thompson, Gillian; Guzman, Lina; Lippman, Laura
Using data from the Programme for International Student Assessment (PISA), we examine the association between parental involvement and student literacy in 21 countries. We consider how the nature of the association between parental involvement and student literacy varies in direction and magnitude across national borders and across multiple dimensions of parental involvement and measures of literacy. Across the 21 countries, we observe that, in general, increased social and cultural communication with parents is associated with higher levels of student literacy, although the association is most consistent in the area of reading literacy. Specifically, for students residing in eight countries (Australia, Austria, Canada, Denmark, Finland, Ireland, Norway and the United Kingdom), there are consistent reading literacy benefits when their parents engage in various forms of social and cultural communication. Consistently across all 21 countries, students have significantly lower literacy scores the more frequently parents assist with homework. This finding provides robust cross-national support for the reactive hypothesis.